Analysis Of Factors Affecting The Use Of Bibit Investment Application - Bobby Irawan*; Sfenrianto Sfenrianto (Universitas Syiah Kuala, 2023)
The development of financial technology, especially in investment, is growing fast. The purpose is to make users more efficient and effective in terms of investment. This study aims to determine and analyze the factors that influence the use of applications from Bibit as an investment application specialized in mutual funds and government bonds. Research method using Technology Acceptance Model (TAM) with some modification in the variables based on the problem faced by the application. The variables used are perceived ease of use, perceived usefulness, responsiveness, perceived risk, social influence, financial literacy, behavioral intention to use, and actual system use. This quantitative research uses questionnaires to 110 Bibit users across Indonesia. The results of the questionnaires will be compiled into combined data to conduct testing on data using validity and reliability tests. Statistical method used with SmartPLS. The results of this study show that the variables perceived ease of use, perceived usefulness, and social influence do not affect the use of the Bibit application. Bibit users are more influenced by financial matters and risks that may arise of using the application. Therefore, the variables of financial literacy and perceived risk have a significant effect with the variables of behavioral intention to use. One of the interesting things about this study is that the variable responsiveness affects perceived usefulness and perceived ease of use variables. It indicates that the ability of the application and the handling of problems from customer service team can affect the perception of usability and ease of application. This study also shows that the behavioral intention to use variable affects the actual use of the application by the user which is denoted by the actual system use variable.